2008
DOI: 10.1118/1.2952643
|View full text |Cite
|
Sign up to set email alerts
|

The extraction of true profiles for TPS commissioning and its impact on IMRT patient-specific QA

Abstract: The aim of this work is to investigate the clinical impact of detector size effect on patient specific intensity-modulated radiation therapy (IMRT) quality assurance (QA). Two photon beam models, BM6 and BM4, were commissioned using photon beam profiles measured with a 6 mm diameter and a 4 mm diameter ion chambers, respectively. A method was developed to extract the "true" cross beam profiles, free of volume averaging effect, using analytic fitting/deconvolution. The method was validated using beam profiles m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(93 citation statements)
references
References 41 publications
5
88
0
Order By: Relevance
“…The method of profile deconvolution used in this work has been previously discussed 12 and is based on the work by Garcia-Vicente et al, 9 and will be discussed briefly here. The measured profile data can be described using the convolution of the detector response function and the true profile from…”
Section: Iib Profile Deconvolution and Beam Profile Fittingmentioning
confidence: 99%
See 2 more Smart Citations
“…The method of profile deconvolution used in this work has been previously discussed 12 and is based on the work by Garcia-Vicente et al, 9 and will be discussed briefly here. The measured profile data can be described using the convolution of the detector response function and the true profile from…”
Section: Iib Profile Deconvolution and Beam Profile Fittingmentioning
confidence: 99%
“…This was considered a good approximation to the true penumbra. 9,12 It is known that diode detectors over respond to the low energy part of the spectrum. Consequently, obtaining the response function using large fields would include the effects of the over response.…”
Section: ͑3͒mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies concerning this specific case clearly show that a broadening of a beam's penumbra can be substantial when comparing measurements using different detectors 4 , 5 , 6 , 7 , 8 , 9 . This effect is also clinically demonstrated by Yan and colleagues (10) . With emphasis placed on the penumbra, methods for reconstructing beam profiles to account for the overestimation of the penumbra are available for ion chambers 10 , 11 , 12 .…”
Section: Introductionmentioning
confidence: 78%
“…Yan et al [17] measured the effect of the detector volume on patient specific IMRT (intensity-modulated radiotherapy) QA and found that the passing rate between calculation and measurement with a Gamma index function [18] increased for a beam model measured with a smaller detector size. The main source of discrepancy between calculated and measured dose distribution was the detector size effect that produces enlarged penumbral widths in the measured data used for RTPS beam modeling [17].…”
Section: Introductionmentioning
confidence: 99%